Socialization of The Effects of Nurses Workload in Preventing The Risk of Falls in Patients at Grandmed Lubuk Pakam Hospital - wati, Syatria; Simarmata, Pratiwi Christa; Hanafi, Muhammad Reza Fahlevi; Syara, Arfah May; Lubis, Yuni Suharnida (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
The quality of nursing services is a value for health services in society. Patients are consumers who always hope to receive good health services. Many incidents may occur if the nurse's workload is too high. To overcome the danger of patients falling, it is necessary to take action to reduce the risk of patients falling. So nurses will always try to prevent patients from falling by installing identification bracelets, triangular labels on patient mattresses, warning signs, adjusting mattress height, and mattress railings. Precautions must also be in accordance with SOP. Nurse workload is the allocation of working time in providing services. The high workload of nurses occurs due to the limited number of staff and uncertain job descriptions. This outreach activity will provide knowledge and courage to communicate about workload so that we can prevent the risk of patient falls. PkM activities were socialized using lecture, question and answer and discussion methods to PkM participants, namely 15 nursing staff. To measure changes in PkM participants' knowledge, pre and post-tests were given to participants. The PkM results show that PkM participants have experienced increased knowledge in preventing the risk of patient falls. Participants also have the courage to discuss with the leadership if the workload is too heavy so that they can get the best solution. Participants also become more diligent in processing their daily work.